430 Wellbeing at work; a european perosh perspective and wellbeing tree. (24th April 2018) - Fishwick, David; Robinson, Edward; Wiezer, Noortje; Mockallo, Zofia; Grosjean, Vincent; Andersen, Lars L
Abstract : Introduction: PEROSH stands for the Partnership for European Research in Occupational Safety and Health. One of the joint research projects run from the PEROSH network deals with Wellbeing at Work, within which scientific representatives from five European countries have developed a set of initiatives aimed at improving working lives. Methods: In order to allow employers and workers to better understand the determinants of wellbeing at work, a model of wellbeing at work was developed, based on scientific knowledge, in three meetings which experts from different fields attended. Results: The WellbeingTree was developed as both a visually attractive and interactive graphic, but also to allow better understanding of wellbeing issues, and their determinants, at work. The tree incorporates abstracts, studies and case studies gathered from the international Wellbeing at Work conferences, but also relies on literature reviews and original articles. The symbol of a tree was adopted because effects of optimising worker wellbeing can be represented as the tree's fruits, and the roots of the tree were designed to represent the precursors, or antecedents, of wellbeing. The roots and branches thus give the user of the tree an opportunity to appreciate the wide variety of influences that may positively, or indeed negatively, influence wellbeing. A variety of sources of feedback about its usefulness have been received, and work is ongoing within PEROSH to develop these further. Discussion: We are now developing the tree further graphically, and it will be populated over time with references to scientific studies and cases. An interactive, 'clickable' version will be developed for use by employers, where clicking on a particular area of the tree will display relevant content. Our European approach to worker wellbeing has successfully developed a tool that we believe will be a useful resource for all those with responsibility for wellbeing of workers.